2013
DOI: 10.1007/s00415-013-7079-8
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa, vitamins, ageing and the neuropathy of Parkinson’s disease

Abstract: Higher prevalence of neuropathy has been described in patients with Parkinson's disease (PD) in comparison with age and gender-matched controls. The cause of neuropathy may be levodopa-induced impairment of vitamin B12 metabolism, suggesting levodopa-naïve subjects should be unaffected. There may, however, be other yet unidentified determinants of neuropathy in PD. We screened 33 consecutive levodopa-naïve PD patients for neuropathy. Demographics, vitamin B12 and folate levels were studied. Findings were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 16 publications
1
34
1
Order By: Relevance
“…The prevalence of B 12 deficiency increases with age 29. This may explain the positive correlation between PNP and age in patients with PD 4 5…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of B 12 deficiency increases with age 29. This may explain the positive correlation between PNP and age in patients with PD 4 5…”
Section: Discussionmentioning
confidence: 98%
“…Levodopa therapy has been identified to be a risk factor for neuropathy (Mancini et al., 2014; Rajabally & Martey, 2013; Toth et al., 2008); however, dose dependency has not yet been studied systematically: one recent study found that IPD patients with neuropathy had an LDD of 1,180 mg, while those without neuropathy had an LDD of 775 mg (Mancini et al., 2014), and like in our study, there were no differences regarding age, gender, and H&Y stage. Our sample, however, had higher LDDs and longer disease durations and therefore very likely a higher exposure to levodopa.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalamin deficiency as a potential cause of neuropathy in IPD has been investigated extensively, but with conflicting results: in levodopa‐treated IPD patients, cobalamin has been shown to be lower in those with neuropathy than in those without it (Ceravolo et al., 2013; Mancini et al., 2014); some researchers have found an association between cobalamin levels and levodopa doses (Rajabally & Martey, 2013; Toth et al., 2010), but this finding could not be confirmed by others (Mancini et al., 2014). Also folate deficiency (Rajabally & Martey, 2013) and levodopa itself, especially LCIG and its ingredients or its way of resorption (Jugel et al., 2013), have been suspected to be involved in the development of neuropathy in IPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levodopa interferes with folic acid metabolism and raises homocysteine. 26 The more levodopa someone is on, the higher the homocysteine level, which increases the risk of dementia. This is especially true in patients with Parkinson's.…”
Section: Dr Mischleymentioning
confidence: 99%